Monday

April 21, 2014

April 21, 2014

Posted by **cheryl** on Friday, March 16, 2007 at 11:48pm.

Hi Cheryl!

The first thing you have to do with this is multiply the -4 into the stuff in the parenthesis.

-4*2x = -8x

-4*-3 = +12

So the left side is -8x+12 = -8x +5

Now that I'm this far along, we see that there's no real answer to this. If we add -8x to both sides, we get:

12=5. And that's clearly wrong.

Either the book/paper/whatever made a mistake in typing this or they are trying to show this question won't work.

So this was a very good question to put up here because it simply doesn't work. Since you had trouble with it, it looks like you probably did it correctly ;-)

**Related Questions**

math, beginning algebra - how do you solve this i've tried many ways and i ...

Math - I have a problem..... -4(2x-3)=-8x+5 I understand first you distribute ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

Calculus - 22. Divide the expression before differentiating. F(x) = (8x^3 - 1...

Math - I need help with figuring out the equation 5(2x+3)-8x=7 5(2x+3)-8x=7 10x+...

math - how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look ...

Derivatives - What is the fourth derivative of f(x)= e^-x^2. I got f''(x)=-2e^-x...

Math correct - Subtract.. (8x^4+5x^3-6)-(2x^2-2x+6) I got 8x^4+5x-2x^2+2x-12 ...

math - can someone correct this for me... solve: -4(2x - 3) = -8x + 5 my answer...